2016
DOI: 10.3109/10826084.2015.1089906
|View full text |Cite
|
Sign up to set email alerts
|

Parental Criminal Justice Involvement and Children's Involvement With Child Protective Services: Do Adult Drug Treatment Courts Prevent Child Maltreatment?

Abstract: Background In light of evidence showing reduced criminal recidivism and cost savings, adult drug treatment courts have grown in popularity. However, the potential spillover benefits to family members are understudied. Objectives To examine: 1) the overlap between parents who were convicted of a substance-related offense and their children’s involvement with child protective services (CPS); and 2) whether parental participation in an adult drug treatment court program reduces children’s risk for CPS involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The results of this study complement two other studies that demonstrated that the children of drug treatment participants, and the broader population of individuals with convictions who are not served by drug treatment courts, are at an elevated risk of being involved with child protective services (Gifford et al 2016) and of having poor academic outcomes (Gifford et al 2015). Given the enormous societal costs of involvement with child protective services, being arrested as a youth, and poor school outcomes (Cohen 1998; Cohen et al 2010; Fang et al 2012; Sum et al 2009), learning how to implement effective prevention strategies is warranted.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results of this study complement two other studies that demonstrated that the children of drug treatment participants, and the broader population of individuals with convictions who are not served by drug treatment courts, are at an elevated risk of being involved with child protective services (Gifford et al 2016) and of having poor academic outcomes (Gifford et al 2015). Given the enormous societal costs of involvement with child protective services, being arrested as a youth, and poor school outcomes (Cohen 1998; Cohen et al 2010; Fang et al 2012; Sum et al 2009), learning how to implement effective prevention strategies is warranted.…”
Section: Discussionsupporting
confidence: 76%
“…Such stress can take an emotional toll and can increase conflict in the home (Conger et al 1994). Parental criminal involvement has been associated with increased risk of children’s mental health problems (Dallaire and Wilson 2010; Phillips et al 2002), child protective services involvement (Gifford et al 2016), and lower school performance (Gifford et al 2015). Moreover, a substantial body of research has found that criminality runs in families—particularly from fathers to sons (Bijleveld and Wijkman 2009; Farrington et al 2001; Hjalmarsson and Lindquist 2012; Junger et al 2013; Rowe and Farrington 1997; van de Rakt et al 2009, 2010; van de Weijer et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Research examining parental involvement across agencies within the criminal justice system is limited (Bartlett et al, 2018). However, these children are identified as being among the most complex cases encountered by child protection agencies (Gifford et al, 2016;Phillips & Detlaff, 2009). Much of the available research focuses on parental imprisonment with minimal consideration of other, or indeed multiple, points of parental involvement in the criminal justice system.…”
Section: Advances and Gaps In The Evidence Basementioning
confidence: 99%
“…Additionally, these parents scored significantly higher on child maltreatment potential, inconsistent discipline and non‐corporal punishment, and significantly lower on parental involvement than matched co‐caregivers who were not involved in the ATC program (Guastaferro et al, 2020). An earlier study documented that ATC participants’ children were at high‐risk of child protective services report and involvement (Gifford, Eldred, Sloan, & Evans, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recognized benefits of parenting and family services for ATC participants, few ATC programs are family centered. As such, existing literature suggests that ATC participation has no effect on child safety outcomes (Gifford, Eldred, Sloan, et al, 2016), child education (Gifford, Sloan, Eldred, & Evans, 2015), or likelihood of children being arrested as young adults (Gifford, Eldred, Evans, & Sloan, 2016). While limited, these studies point to a missed opportunity for intervention to improve the participants’ and future generations’ outcomes.…”
Section: Introductionmentioning
confidence: 99%